Interaction of Fullerenes with Organosilanes in the Ionization Chamber of a Mass Spectrometer under Electron Impact and the Reaction of C60 with Tetraphenylsilane in Solution under UV Irradiation - Yury I. Lyakhovetsky; Elena A. Shilova; Alexandra P. Pleshkova; Alexander I. Belokon; Sergey O. Yakushin; Boris L. Tumanskii (Journal of Spectroscopy)
C60 was shown to react with organosilanes Me4Si, Ph2SiH2, Ph2MeSiH, Ph4Si, and α-naphthylphenylmethylsilane in the electron ionization ion source of a mass spectrometer with the transfer of the corresponding organic radicals (Me, Ph, and α-naphthyl) from the silanes to the fullerene. The reactions were accompanied by hydrogen addition to some products and hydrogen loss from them. C70 reacted with Me4Si analogously. A reaction mechanism involving homolytic dissociation of the silanes under electron impact to the corresponding organic radicals, which react further with C60 at the surface of the ionization chamber of the mass spectrometer to give the respective adducts, was offered. A mechanistic study of the reaction of C60 with Me4Si supported it. No silicon containing derivatives of the fullerenes were found. C60 reacted with Ph4Si in solution under UV irradiation in a similar fashion furnishing phenyl derivatives of the fullerene. These results provide an additional support to the hypothesis formulated earlier that the homolytic reactive mass spectrometry of fullerenes (the reactions of fullerenes with other species in the ionization chambers of mass spectrometers and their mass spectral monitoring) can predict the reactivity of them toward the same reagents in solution to a significant extent.